Affective symptoms across the life course and resilience in cognitive function - Georgia Bell; Amber John; Darya Gaysina (Taylor & Francis Group, 2020)
Background: Little is known about what factors can modify the relationship between affective symptoms and cognitive function across the life course. Aim: To investigate a number of factors that can contribute to resilience in cognitive function in relation to affective symptoms, using data from the National Child Development Study. Subjects and methods: Adult affective symptoms were measured using the Malaise Inventory Scale (ages 23, 33, 42 and 50). Measures of immediate and delayed memory, verbal fluency and information processing accuracy (age 50) were used to derive measures of resilience in cognitive function-better than predicted cognition, when accounting for experiences of affective symptoms. Factors contributing to resilience in cognitive function were informed by a literature review and included sex, childhood cognitive ability, education, household socio-economic position (SEP), midlife SEP, and APOE genotype. Linear regression and structural equation modelling approaches were used for analyses. Results: Higher childhood cognitive ability, educational level, midlife SEP and female sex contributed to better than predicted cognitive function in relation to affective symptoms (i.e. resilience), with particularly consistent effects for memory. No effects on resilience were revealed for APOE genotype. Conclusion: Understanding factors contributing to resilience in cognitive function in those with affective symptoms can inform interventions to promote healthy cognitive ageing for those at risk.